Accelerated hygrothermal aging of bond in FRP-masonry systems - Ghiassi, Bahman (2015)
This paper addresses the results of accelerated hygrothermal (coupled temperature and moisture) tests on FRP-strengthened clay bricks aimed at investigating bond degradation mechanisms. The exposures are selected to simulate different environmental conditions and the bond degradation is periodically investigated by visual inspection and by conventional single-lap shear bond tests. The changes in the properties of material constituents have also been monitored and the results are presented and critically discussed. A decay model is then adopted for simulating the observed degradation in the specimens. The model, once validated, is used for long-term performance prediction of FRP-masonry systems and the results are compared with the environmental reduction factors proposed by available design guidelines.